2008
DOI: 10.1111/j.1582-4934.2008.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagomir-mediated silencing of endothelial cell specific microRNA-126 impairs ischemia-induced angiogenesis

Abstract: MicroRNAs are negative regulators of gene expression that play a key role in cell-type specific differentiation and modulation of cell function and have been proposed to be involved in neovascularization. Previously, using an extensive cloning and sequencing approach, we identified miR-126 to be specifically and highly expressed in human endothelial cells (EC). Here, we demonstrate EC-specific expression of miR-126 in capillaries and the larger vessels in vivo. We therefore explored the potential role of miR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(183 citation statements)
references
References 27 publications
8
170
1
4
Order By: Relevance
“…Currently, miR-126, the miR-17-92 cluster, let-7b and -7f, miR130a, miR-210, miR-378, and miR-296 are known as proangiogenic miRNAs, while anti-angiogenic miRNAs include miR-221/miR-222, miR-328, miR-15b, miR-16, miR-20a, and miR-200b (Chan et al, 2011;Wu et al, 2009). Among proangiogenic miRNAs, miR-126 is highly expressed in human endothelial cells (van Solingen et al, 2009;Wang et al, 2008). Recent studies showed that pro-angiogenic function of miR-126 is in part mediated by down-regulating Sprouty-related protein SPRED1 and phosphoinositol-3 kinase regulatory subunit 2 (PIK3R2/p85-β), which are inhibitors of angiogenic signaling (Fish et al, 2008;Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, miR-126, the miR-17-92 cluster, let-7b and -7f, miR130a, miR-210, miR-378, and miR-296 are known as proangiogenic miRNAs, while anti-angiogenic miRNAs include miR-221/miR-222, miR-328, miR-15b, miR-16, miR-20a, and miR-200b (Chan et al, 2011;Wu et al, 2009). Among proangiogenic miRNAs, miR-126 is highly expressed in human endothelial cells (van Solingen et al, 2009;Wang et al, 2008). Recent studies showed that pro-angiogenic function of miR-126 is in part mediated by down-regulating Sprouty-related protein SPRED1 and phosphoinositol-3 kinase regulatory subunit 2 (PIK3R2/p85-β), which are inhibitors of angiogenic signaling (Fish et al, 2008;Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…1B and C). As the purity of CD14 ϩ monocytes in our study exceeded 97% based on CD14 staining, the predominant miR-126-5p quantified was likely derived from monocytes, although we were unable to exclude the possibility of contamination by predominant endothelial cells (ECs), which have been reported as the main source of the miR-126-3p/5p cluster (35)(36)(37)(38).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a significant increase in several miRNAs in monocytes was observed in HIV-1 infection, among which miR-126-5p was the most upregulated member, especially in proinflammatory CD14 ϩ CD16 ϩϩ monocytes. The miR-126-3p/5p cluster is expressed predominately in ECs (35)(36)(37)(38) and can exert their functions in non-ECs (34,56,57). miR-126-5p has been shown to correlate with metastasis-free survival in breast cancer patients (33) and to promote endothelial proliferation and prevent atherosclerosis by suppressing delta-like 1 (Dlk1) (58).…”
Section: Mir-126-5p Enhances Monocyte Responses To Lpsmentioning
confidence: 99%
“…miR-126 has been found to mediate CXCL12 production, which was enriched in apoptotic bodies, and induced vascular protection by repressing the function of the regulator of G protein signaling 16 (21). In addition, the beneficial role of miR-126 has been elucidated using the specificity of antagomir-induced silencing of miR-126 in vivo (22).…”
Section: Endothelial Cells and Mirnasmentioning
confidence: 99%